2021
DOI: 10.3390/s21186285
|View full text |Cite
|
Sign up to set email alerts
|

Motor-Imagery EEG-Based BCIs in Wheelchair Movement and Control: A Systematic Literature Review

Abstract: The pandemic emergency of the coronavirus disease 2019 (COVID-19) shed light on the need for innovative aids, devices, and assistive technologies to enable people with severe disabilities to live their daily lives. EEG-based Brain-Computer Interfaces (BCIs) can lead individuals with significant health challenges to improve their independence, facilitate participation in activities, thus enhancing overall well-being and preventing impairments. This systematic review provides state-of-the-art applications of EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 111 publications
(213 reference statements)
0
23
0
1
Order By: Relevance
“…This hypothesis was supported by topological analyses of the EEG signals which showed that the global asset of brain activities during actual and imaginatively rotated posture of the head were significantly more similar between each other in highs than in lows [12]. Theoretically, together with the highs' greater motor cortex excitability [13], these hypnotizability-related characteristics could make highs more prone than the general population to take advantage from imagery training and brain-computer interface (BCI) interventions [27].…”
Section: Functional Equivalence Between Imagery and Perception/action...mentioning
confidence: 90%
“…This hypothesis was supported by topological analyses of the EEG signals which showed that the global asset of brain activities during actual and imaginatively rotated posture of the head were significantly more similar between each other in highs than in lows [12]. Theoretically, together with the highs' greater motor cortex excitability [13], these hypnotizability-related characteristics could make highs more prone than the general population to take advantage from imagery training and brain-computer interface (BCI) interventions [27].…”
Section: Functional Equivalence Between Imagery and Perception/action...mentioning
confidence: 90%
“…In recent years, the Brain-Computer Interface application has been growing rapidly, establishing itself as an emerging technology [ 87 ] tested in several scenarios such as rehabilitation [ 88 ], robotics [ 89 ], precision surgery and speech recognition. However, the usability of many professional brain-sensing equipment remains limited.…”
Section: Ms Hololens 2 Applications In Medical and Healthcare Context...mentioning
confidence: 99%
“…814–826). EEG and fMRI belong to the non-invasive BCI systems, and intracortical recording and ECoG are the two invasive modalities mainly used in BCI research [ 7 ] (p. 6285). This research focused on the non-invasive EEG-based BCIs that have been realized using a variety of paradigms, including steady-state visual evoked potential (SSVEP), P300, rapid serial visual presentation (RSVP), movement-related potentials (MRPs), motor imagery [ 8 , 9 , 10 ], etc.…”
Section: Introductionmentioning
confidence: 99%